INNOVATIVE APPROACHES TO THE USE OF FEEDBACK TECHNIQUES IN THE EDUCATIONAL PROCESS OF HIGHER EDUCATION INSTITUTIONS - Chervinska, Inna; Vasylyk, Maryna; Neyko, Nila; Chervinskyi, Andrii (Mountain School of Ukrainian Carpaty, 2023)
The authors formulate the essence of feedback, describe the organisational and didactic conditions for its effective provision in the educational process of a higher education institution. The authors propose to consider feedback in two aspects: as an option for establishing successful communication and interaction between the teacher and the higher education applicant, and as an option for effective feedback for assessing academic achievements and controlling the knowledge of higher education applicants. The article emphasises the recognition of the importance of the correct application of feedback techniques in the educational process, since it can have both a positive and a negative impact on the organisation of the educational process and the success of higher education applicants. The blended learning format, unlike other modern forms of organising the educational process, involves the use of remote access mode, which usually makes it impossible to communicate and interact directly between the teacher and the education applicants. It is noted that feedback should be considered in the context of the educational component where it is applied. The researchers note that feedback is a means of obtaining important information, the results of educational activities necessary for the effective management of the educational process in a blended learning format. It is noted that the purpose and main objectives of the study are to reveal innovative approaches and organisational and didactic conditions for the use of feedback techniques in the educational process of a higher education institution. The authors point out that innovative ideas of feedback techniques are successfully implemented in the modern educational space of Ukraine. It is emphasised that the effectiveness of implementing feedback techniques in higher education institutions depends on the context, goals, objectives and content context of education and upbringing of a growing personality. The concept of feedback is considered by many sciences within the framework of different scientific approaches and directions, since it mostly has a different interpretation and meaning, as it is one of the main elements of the functioning of the educational system.